Las de medidas de protección administrativas en el marco de la ley orgánica de prevención y erradicación de violencia contra la mujer; y, su aplicación frente a los Derechos Humanos del presunto infractor - Palomo Guamaní, Flavio Marcelo (2024)
Violence against women has been and is a social problem that demands a response of protection in the legal framework, from the international standard we have treaties and international agreement; In the case of Ecuador, the Organic Law of Prevention and Eradication of Violence against Women, provides protection measures administrative; that are the subject of a dissertation to determine the violation of human rights of the alleged offender, from misuse of the measures applied by the victim or complainant. In use of research methodology legal, from the qualitative method the legal phenomenon; while, from a quantitative perspective, statistics are sources to determine the variable characteristics of the event for its interpretation. The Authorized administrative bodies are the Cantonal Protection Boards of Rights, Political Tenures and National Commissioners. To then be known by the judicial authority, the Judge, who must ratify, modify or revoke the administrative protection measures applied; Therefore, it is necessary to analyze the affectation of the Human Rights that assist the alleged offender, if complies with due process in the right to evidence, affects legal certainty, effective judicial protection and the principle of presumption of innocence.